2018
DOI: 10.1007/s00253-018-8914-8
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of wine: clarifying the role of microorganisms

Abstract: The concept of wine complexity has gained considerable interest in recent years, both for wine consumers and wine scientists. As a consequence, some research programs concentrate on the factors that could improve the perceived complexity of a wine. Notably, the possible influence of microbiological factors is particularly investigated. However, wine complexity is a multicomponent concept not easily defined. In this review, we first describe the actual knowledge regarding wine complexity, its perception, and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 111 publications
3
47
1
3
Order By: Relevance
“…The analysis of the microbiological data allows some consideration about the oenological implication of the observed evolution of microbiota. The evolution of the yeast population seems to follow the trend already observed by many authors (Tempere et al ), while in the case of bacteria we observed the presence of a remarkable biodiversity that differs from data reported in the literature (Bartowsky ; Pinto et al ; Liu et al ). Usually it is believed that in wine only lactic and acetic acid bacteria are capable of surviving.…”
Section: Discussionsupporting
confidence: 56%
“…The analysis of the microbiological data allows some consideration about the oenological implication of the observed evolution of microbiota. The evolution of the yeast population seems to follow the trend already observed by many authors (Tempere et al ), while in the case of bacteria we observed the presence of a remarkable biodiversity that differs from data reported in the literature (Bartowsky ; Pinto et al ; Liu et al ). Usually it is believed that in wine only lactic and acetic acid bacteria are capable of surviving.…”
Section: Discussionsupporting
confidence: 56%
“…More recently, NS wine yeasts have received special attention by winemakers due to the search of different and desired oenological characteristics, compared to SC commercial strains. Diverse secondary metabolic pathways and higher enzymatic activities (esterases, β-glycosidases, lipases, and proteases), result in sensory complexity [1,51,52] that might contribute to an increased diversity of 'flavor phenotypes'. The 'flavor phenotype' is an interesting concept for yeast selection, considering that now more than 1300 volatile compounds can be determined in wine [2,53].…”
Section: Hanseniaspora/kloeckera Strains and Flavor Compoundsmentioning
confidence: 99%
“…Furthermore, the wine market's demand for wines with increased sensory properties, such as aromatic complexity and varietal typicity, has turned interest towards non-Saccharomyces (nSc) and other nonconventional yeast species (Fleet, 2008;Sadoudi et al, 2012;Albertin et al, 2019). The nSc yeasts are characterised by high genetic diversity,and some species and strains can be detrimental to wine quality, while others can be beneficial (Renault et al, 2009;Tempère et al, 2018). Representative genera of the latter category detected in early fermentations are Metschnikowia, Candida, Hanseniaspora, Rhodotorula and Pichia (König and Berkelmann-Löhnertz, 2017).…”
Section: Introductionmentioning
confidence: 99%